The Impact of Fulfilling Social Needs in Anime Yagate Kimi ni Naru - Sholihah, Rivany Destie; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze the impact of social needs between the characters Koito Yuu and Touko Nanami in the anime Yagate Kimi Ni Naru. This research uses descriptive analysis method with psychological approach using Abraham Maslow’s Hierarchy of Needs theory. The material object of the research is the anime Yagate Kimi Ni Naru. The formal object is the impact of social needs between the characters Koito Yuu and Touko Nanami in the anime Yagate Kimi ni Naru. Data collection techniques used listening and note-taking techniques. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. Through the research, it was found that the fulfillment of social needs between the character Koito Yuu and the character Touko Nanami had an impact on the birth of behaviors outside the norms that tended to same-sex attraction behavior. The results of the research become a description of psychological symptoms in literary works.